Implementasi Pasal 3 Peraturan Walikota Pekanbaru Nomor 44 Tahun 2014 Tentang Program Pemberdayaan Masyarakat Berbasis Rukun Warga Di Kecamatan Binawidya Tahun 2020-2023 - Rahmawati, Moulidiah; Deliana, Evi; Zulwisman, Zulwisman (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Community Empowerment Program Based on Community Associations (PMB-RW) is one of the superior policies. The aim of writing this thesis is firstly, to find out the implementation of Article 3 of Pekanbaru Mayor Regulation Number 44 of 2014 in Binawidya District for 2020-2023. The two inhibiting factors in implementing Mayor Regulation Number 44 of 2014 in Binawidya District for 2020-2023. The three are efforts to overcome obstacles in the implementation of Pekanbaru Mayor Regulation Number 44 of 2014 in Binawidya District for 2020-2023. This type of research is empirical juridical. From the results of research on the problem, there are three main things that can be concluded. First, the implementation of Article 3 of the Pekanbaru Mayor's Regulation Number 44 of 2014 concerning Community Empowerment Programs Based on Community Associations in Binawidya District has experienced a few obstacles and has not been fully implemented properly. The socialization has not been carried out thoroughly, so it has received little support from related parties. Second, factors inhibiting the implementation of Article 3 of Pekanbaru Mayor's Regulation Number 44 of 2014 concerning Community Empowerment Programs Based on Community Associations in Binawidya District for 2020-2023 include the lack of budget and lack of participation from the people of Binawidya District. Third, efforts made to overcome obstacles include efforts that have been made, efforts that are being made and efforts that will be made. The author's suggestion is that the government, especially in Binawidya District, should be more active and productive in socializing community empowerment programs based on community associations by further optimizing training and physical development to the maximum.